Nilai Religi Dari Cerita Rakyat Saridin - Abelia Helga Natasya; Aulia Rohmah; Sania Rizka Faiza; Mohammad Kanzunnudin (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research uses qualitative research methods to analyze "character values ​​from the Saridin folklore". Shows that the story "Saridin" contains values ​​such as divinity, nationalism, independence and mutual cooperation. These values ​​develop good character and skills. Saridin Folklore on the coast, especially in Pati, still remains strong in society because the process of cultural reproduction is still ongoing through art, literary works and local traditions. However, he is also known as a strong person because he expresses truth and justice in ways that often violate common norms. Saridin is considered to represent the critical wisdom of Javanese coastal communities. He upholds six main values, namely sincerity, patience, obedience to teachers and parents, honesty, concern for the environment, and faith in the power of God. This is in accordance with the demands of character education which emphasizes the importance of cultural awareness and cultural intelligence, as does Saridin.